The Role of Renewable Energy in the Transition to a Low-Carbon Energy System in Indonesia - Yifan Tang; Antony Antony (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The role of renewable energy in the transition process towards a low-carbon energy system in Indonesia is very crucial. The transition to a sustainable energy system is an urgent need to address global climate change and dependence on fossil fuels. In the context of Indonesia, a country with abundant natural resources, the use of renewable energy has great potential. Renewable energy such as solar, wind, hydro and biomass energy can provide an alternative that is environmentally friendly and sustainable to meet national energy needs. The purpose of this study is to obtain a mapping of the role of low-carbon renewable energy in Indonesia. This study explores various policies and strategic steps that need to be taken by the government, private sector, and the people of Indonesia to integrate renewable energy into the national energy system. From the research results it was found that the contribution of renewable energy has an economic and social impact on Indonesian society. In addition, it was also found that the contribution of renewable energy can work if it has government support. Moreover, with the right adoption, renewable energy can contribute significantly to reducing carbon emissions, increasing energy independence, creating new jobs, and encouraging sustainable economic growth in Indonesia. This study also analyzes the challenges and opportunities faced in implementing renewable energy, as well as provides policy recommendations to accelerate the transition to a more sustainable, low-carbon energy system in Indonesia.